INFLUENCE OF CHRONIC MILD STRESS ON RATH BEHAVIOR UNDER EXPERIMENTAL PHARMACOTHERAPY - Kharchenko Y. V.; Abramov S. V.; Kryzhanovskyi D. H.; Fedchenko M. P.; Chernenko H. P.; Filipenko V. V.; Tereshchenko N. M. (Вісник проблем біології і медицини, 2022)
. Introduction. Vulnerability to developing mood disorders, such as anxiety disorders and depression, depends on a combination of genetic and environmental factors, among which stress plays a significant role. It is interesting that coping with stress is influenced by the level of the biological response to stress and related neuroendocrine systems, active coping with stress is increased with the help of antidepressants. This indicates that drugs that affect the biological side of stress resistance can increase the effectiveness of existing treatment methods and preventive care. The gut microbiome is a biological factor that may also influence resistance to stress. The broad impact of the gut microbiota on human health, including mental health, has begun to be recognized and understood over the past decade. The aim of the study was to determine the effect of chronic mild stress (CMS) on the development of emotional and behavioral disorders under the conditions of experimental pharmacotherapy in rats. Materials and methods. The study was carried out on 24 male Wistar rats weighing 230–250 g. The basis of the modeling of chronic muscle stress was based on the classic method of Willner, adapted to the conditions and purpose of our experiment. The animals of the experimental groups were subjected to daily exposure to weak stressors alternating with a 168-hour (7-day) cycle of changes in these stimuli for 4 weeks. Animals were randomly divided into five groups (n=8 in each). I – negative control, II – positive control (CMS). Group III rats for 28 days of the experiment received intragastric combination therapy – a symbiotic combining the prebiotic Lactulose (Lac) and a probiotic containing 4 billion active cells (CFU)): Lactobacillus acidophilus, Lactobacillus rhamnosus, Streptococcus thermophilus, Lactobacillus delbrueckii subsp. Bulgaricus (Yo). Group IV animals also received intragastric vitamin D3 (vit. D3 ). Group V received triple combination pharmacotherapy, which included yogurt / lactulose + vitamin D3 in the above doses. The results of the study showed significant changes in the positive control group. The rate of crossing in rats was 12.3% lower than the group of negative control. These rats showed a statistically significant decrease in the number of peeping into holes by 44.4%. It was also characterized by a decrease in the number of vertical rises by 35.3% compared with the negative control group. The latency of the exit from the center of the open field in positive control group rats was 22.2% lower than in negative control animals. The reaction to novelty in CMS rats tended to decrease. In animals treated with vit. D3 , compared with the group of animals with CMS, on the 28th day of the study there was a statistically significant increase of 245.5% and 260.0%, respectively, rearing and research activity. It should be noted that under these experimental conditions, administration of the study drug led to a decrease of 100.0% acts of defecation, which indicates a decrease in animal anxiety. The number of grooming acts tended to increase, which indicated a positive effect of the drug on the emotional state of animals. The latency of the exit from the center of the open field in rats treated with vit. D3 was 114.3% higher than in animals with CMS. The reaction to novelty in rats of this group increased. In animals treated with a combination of vit. D3 with Yo + Lac, compared with the group of animals with CMS there was a statistically significant increase by 209.1% of rearing and crossing by 97.2%. It should be noted that under these experimental conditions, the administration of the study combination led to a decrease of 75.0% acts of defecation, which indicates a decrease in animal anxiety. The number of grooming acts tended to increase, which indicated a positive effect of the combination on the emotional state of the animals. Results. Therefore, based on the studies, it can be concluded that chronic mild stress changes the behavior of rats in the open field test, which is characterized by significant inhibition of motor and research activity of experimental animals. Administration of probiotic and prebiotic, both alone and in combination with vitamin D3 , changed the rates of behavioral responses in the open field test in rats on the background of emotional disorders. Conclusion. Chronic stress changes the behavior of rats in the open field test, which is characterized by significant inhibition of motor and research activity of experimental animals and symbiotic drugs with vitamin D3 can be a significant lever in the correction of this condition.